Development of a conversation approach for practice nurses aimed at making shared decisions on goals and action plans with primary care patients - Stephanie Anna Lenzen; Ramon Daniëls; Marloes Amantia van Bokhoven; Trudy van der Weijden; Anna Beurskens (BMC, 2018)
Abstract Background Primary care nurses play a crucial role in setting personal goals and action plans together with chronically ill patients. This may be a challenge for practice nurses, who are often trained to adopt protocol-based work routines. The aim of this study was to systematically develop a conversation approach, and a corresponding training course, for practice nurses aimed at making shared decisions about goals and actions with their chronically ill patients. Methods The 6-step iterative Intervention Mapping protocol was used as a framework. This paper describes the first four steps of the protocol. After the first step, in which literature studies as well as qualitative studies were conducted, the overall aim and objectives for the approach were formulated (step 2). In step 3, methods and strategies for the approach were chosen, which were translated into practical components in step 4. In addition, a pilot study was conducted. Results The main objectives of the approach focus on the ability of practice nurses to explore the patients' perspectives from a holistic point of view, to explicitly formulate goals and action plans, to tailor shared decision making about goals and action plans to individual patients, and to continuously reflect on work-related attitudes. The approach consists of a practical framework for shared decision making about goals and actions. The framework involves a tool for exploring patients' perspectives and a tool for identifying patient profiles, to facilitate tailoring shared decision making. A comprehensive training course for practice nurses was developed. Conclusion We systematically developed a conversation approach, involving a practical framework with several tools, which aims to support practice nurses in making shared decisions about goals and actions with their patients. As practice nurses need support in their learning process to be able to share decisions with patients, we also developed a comprehensive training course for them. The approach and the training course were developed in close collaboration with important stakeholders. Some critical factors for the implementation of the approach were revealed. These factors will be addressed in the next step, a process evaluation (not part of this paper).